Integration of Theology, Education, and Activism: Exploring Eco-Theological Discourse and Muhammadiyah’s Environmental Engagement - Pratama, Sandi; Masuwd, Mowafg Abrahem (EDUKASIA, 2025)
Environmental degradation and climate change are urgent ethical and theological challenges prompting faith-based responses. In Islam, the principles of tauhid (oneness), khilafah (stewardship), and amanah (sacred trust) are reframed into an ecological ethic affirming environmental care as a religious duty. This study aims to explore how Muhammadiyah constructs its eco-theological discourse by analyzing peer-reviewed works from 2021 to 2024 through an integrative literature review and summary matrix. The analysis identifies three core dimensions: theology, education, and activism. Muhammadiyah expands al-Ma’un theology to include ecological justice, embeds environmental values in educational institutions, and promotes activism through legal advocacy, fatwas, and grassroots movements. These efforts position Muhammadiyah as an ethical force in environmental governance. Findings reveal a holistic, replicable model integrating theology, education, and civic action. The study also acknowledges limitations, including limited institutional resources and the absence of empirical evaluation of long-term impacts.